Mesenchymal stem cell therapy for ischemic stroke: Novel insight into the crosstalk with immune cells - Tan, Nana; Xin, Wenqiang; Huang, Min; Mao, Yuling (Frontiers in Neurology, 2022)
Stroke, a cerebrovascular accident, is prevalent and the second highest cause of death globally across patient populations; it is as a significant cause of morbidity and mortality. Mesenchymal stem cell (MSC) transplantation is emerging as a promising treatment for alleviating neurological deficits, as indicated by a great number of animal and clinical studies. The potential of regulating the immune system is currently being explored as a therapeutic target after ischemic stroke. This study will discuss recent evidence that MSCs can harness the immune system by interacting with immune cells to boost neurologic recovery effectively. Moreover, a notion will be given to MSCs participating in multiple pathological processes, such as increasing cell survival angiogenesis and suppressing cell apoptosis and autophagy in several phases of ischemic stroke, consequently promoting neurological function recovery. We will conclude the review by highlighting the clinical opportunities for MSCs by reviewing the safety, feasibility, and efficacy of MSCs therapy.